The logic EQ has four inference rules
(1) Substitution
EE[v:=F]
where E is an expression, v is a list of variables and F is a corresponding list of expressions.
Iow, if E is a theorem, so is E with all the variables in V replaced by the corresponding expressions in F.
E.g: Let E be 2.x/2 = x be a theorem.
Then by substitution, so is 2.(j + 5) / 2 = j + 5 where v=x and E = j+5
(2) Leibniz
X=YE[z:=X]=E[z:=Y]
NB: z is a variable, NOT an expression.
Two ways of looking at Leibniz
(A) Given an equality X = Y and an expression E,
(1) Choose a variable z within E
(2) Replace the equality with a new equality with z replaced by X on one side and Y on the other
(B) Given E,
(1) spot an *expression X* (NOT variable ) within E that needs replacement
(2) Find an equality X = Y
(3) consider the given expression E to be actually E [z := X]
(4) Use Leibniz with the equality (from (2) ) to get E [z := Y]
this is written as
E[z:=X]
= Leibniz. z is z. X = Y
E[z:=Y
eg:
Given m = 2j (note: this is the equality X = Y) and E is m/2 = 2.(j - 1) prove that 2j/2 = 2(j-1)
Leibniz usage B: m on the LHS of E needs to be replaced with 2j, so we look for an equality with m on the left side, which we find in the given equality. If we consider the LHS of E to be E[z := m], then
m/2=2(j−1)
= Leibniz. z is m, m = 2j
2j/2=2(j−1)
(C) Combined use of Substitution and Leibniz
Strictly speaking, Substitution and Leibniz are distinct inference rules and the two should be used distinctly
Given we know that 2x/2 = x (note: this is the equality X=Y)
let E be 2j/2 = 2(j+1). prove j = 2(j-1 )
(separate use of Substitution and Leibniz)
E≡ 2j/2 = 2(j - 1)
= Substitution j := x
2x/2 = 2(x - 1)
= Leibniz z is 2x/2 with equality 2x/2 = x
x = 2(x - 1)
= Substitution x := j
j = 2(j - 1) QED
(simultaneous use of Substitution and Leibniz collapses some steps)
E≡ 2j/2 = 2(j - 1)
= Substitution and Leibniz 2x/2:= x
j = 2(j - 1) QED
(3) Transitivity
X=Y,Y=ZX=Z
iow if X = Y and Y = Z are theorems, so is X = Z
(4) Equanimity
E,E=FF
iow a theorem is either an axiom or the result of an inference rule where the premises are axioms
Example for use of all 4 inference rules
Prove that ¬p≡p≡false
Proof:
(0) ¬p≡p≡false
(1) = Leibniz and Substitution with Theorem ¬(x≡y)≡¬x≡y used in the reverse direction, substituting x,y := p,p and z = ¬p≡p
(2) ¬(p≡p)≡ false
(3) = Leib + Sub using Theorem Identity of ≡,x≡x≡ true , z is p ≡ p, and x := p
(4) ¬true≡false
(3) = is an Axiom and therefore
(5) true QED
and since (0) = (2) and (2) = (4) and (4) = (5), by Transitivity (0) = (4)
and since (0) = (4) and (4) is a theorem, (0) is a theorem by Equanimity.
No comments:
Post a Comment